Multidisciplinary Inpatient Rehabilitation for Unilateral Neuromyelitis Optica: Case Report - Antonio Vintimilla; Abigail Rekieta (Clinical Case Reports)
ABSTRACT Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune condition that typically affects middle‐aged females and presents with bilateral neurological symptoms. Unilateral presentations are uncommon and often difficult to diagnose. Due to its low incidence, rehabilitation strategies for NMOSD remain understudied, particularly in patients with atypical presentations. This report describes a 34‐year‐old African American male with a unilateral presentation of seropositive NMOSD. He was admitted to inpatient rehabilitation with significant functional impairments and reduced independence across self‐care and mobility tasks. A multidisciplinary, high‐intensity rehabilitation program was implemented, incorporating task‐specific training and conventional therapies, along with more unconventional interventions such as manual therapy and dry needling. Throughout his stay, the patient progressed steadily in balance, transfers, gait, and daily activities. At discharge, he demonstrated significant improvements in all self‐care and functional mobility scores, reflecting meaningful gains in independence. Further research is needed to explore long‐term outcomes and to determine optimal rehabilitation strategies for individuals with NMOSD, particularly those with atypical or focal clinical features.